2012
DOI: 10.1037/a0026312
|View full text |Cite
|
Sign up to set email alerts
|

Chronic threat and contingent belonging: Protective benefits of values affirmation on identity development.

Abstract: Two longitudinal field experiments in a middle school examined how a brief "values affirmation" affects students' psychological experience and the relationship between psychological experience and environmental threat over 2 years. Together these studies suggest that values affirmations insulate individuals' sense of belonging from environmental threat during a key developmental transition. Study 1 provided an analysis of new data from a previously reported study. African American students in the control condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
253
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(277 citation statements)
references
References 68 publications
21
253
2
1
Order By: Relevance
“…One driver, it seems, was a stronger sense of belonging in school, which is among the most important psychological determinants of student success (12,25). As previously reported (25), African Americans had a stronger sense of belonging in middle school in the affirmation condition than in the control condition. Stronger belonging partially mediated the long-term effect of affirmation on African Americans' enrollment in a 2-or 4-y college, over and above baseline belonging (SI Appendix, Fig.…”
Section: -Year College Selectivitysupporting
confidence: 52%
See 1 more Smart Citation
“…One driver, it seems, was a stronger sense of belonging in school, which is among the most important psychological determinants of student success (12,25). As previously reported (25), African Americans had a stronger sense of belonging in middle school in the affirmation condition than in the control condition. Stronger belonging partially mediated the long-term effect of affirmation on African Americans' enrollment in a 2-or 4-y college, over and above baseline belonging (SI Appendix, Fig.…”
Section: -Year College Selectivitysupporting
confidence: 52%
“…At another middle school with a predominantly Latino American minority population, the same affirmation activities improved the academic grades of Latino American students over the course of 3 y (15). Consistent with self-affirmation theory, minority students who had completed the self-affirmation exercises were less likely to display drops in academic belonging and motivation at times of difficulty in school (15,25).…”
mentioning
confidence: 62%
“…According to one facet of the model, affirmation enables people to untether threats from the self by promoting self-evaluations that are independent of the potential threat (Sherman & Kim, 2005;Cook, Purdie-Vaughns, Garcia, & Cohen, 2012;Sherman et al, 2013). The present studies found support for this aspect of the model in the analysis of self-feelings (Study 1) and feelings of self-worth (Study 2).…”
Section: Untethering Threats From the Selfsupporting
confidence: 61%
“…Understanding the root cause of the problem in terms of the need to belong made a brief intervention extremely effective [30]. Related developmental research has shown that a sense of belonging to a group can enhance achievement motivation in preschool children [25], suggesting that work on belonging can have important implications for educational research [114].…”
Section: (B) Enhancing Social Inclusionmentioning
confidence: 99%